Study of a methodology to evaluate the severity of obstructed coronary arteries with the aid of computer simulations. - Yamabe, Paulo Vinícius Miyuki (2016)
Computer simulations have become a great tool to assist the medical field. The present work is a study of a non-invasive patient-specific methodology to evaluate the hemodynamic importance of coronary stenosis using computer simulations. The severity of the lesion is evaluated by the Fractional Flow Reserve, calculated by the pressure gradient before and after the lesion. The geometry models are obtained from medical images of Computed Tomography Angiography exams, and the simulations considers the pulsatile flow and the blood as a non-Newtonian fluid. The governing equations of the blood flow are solved by using Finite Element Method applied to the numerical method called Incremental Pressure Correction Scheme, and with the aid of the libraries from the open-source software FEniCS. Computer simulations of three different patients are performed and the results are compared with the invasive FFR measurements. The methodology proposed shows to be feasible in the study and analysis of stenosed coronaries.